2012
DOI: 10.1590/s1984-29612012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal helminths in calves and cows in an organic milk production system

Abstract: The main aim of this study was to determine the distribution of populations of gastrointestinal helminths in lactating crossbred cows and calves during the grazing season in an organic milk production system. In addition, the potential importance of the peripartum in relation to the parasite load was examined. Between January 2007 and December 2008, parasitological fecal examinations were performed on cattle belonging to the Integrated Animal Production Program of Embrapa Agrobiology. The cows' parasite load r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
2
3
0
1
Order By: Relevance
“…(29.7%) were the most frequently observed GIN. A similar finding was reported in ruminants but with slight difference in the predominant genera [26,29,30]. In spite of numerical difference observed in fecal egg count between treated groups but not statically significant (p ˃ 0.05), there was a negative correlation between mean fecal egg count in each group and the days posttreatment.…”
Section: Discussionsupporting
confidence: 85%
“…(29.7%) were the most frequently observed GIN. A similar finding was reported in ruminants but with slight difference in the predominant genera [26,29,30]. In spite of numerical difference observed in fecal egg count between treated groups but not statically significant (p ˃ 0.05), there was a negative correlation between mean fecal egg count in each group and the days posttreatment.…”
Section: Discussionsupporting
confidence: 85%
“…Helminth infections were more common during the wet season than the dry season in our study. This is not novel as researchers elsewhere in the world has reported similar findings [1,2,36,41,42]. Our observation may be attributed to the high moisture content and lower temperature which favors the growth and development of helminth eggs and larvae on pasture, leading to infections in cattle.…”
Section: Discussionsupporting
confidence: 84%
“…Trichostrongylus spp. has the ability to withstand more hostile seasons which facilitates both survival and reinfection all year round [36]. To these, we observed that helminth species were recorded in a noticeable prevalence among cattle throughout the year.…”
Section: Discussionmentioning
confidence: 81%
“…Dados registrados na literatura comprovam que a ocorrência de parasitismo em bovinos pode variar, de região para região, dentro do Brasil. Região Sul: 18 a 84,85% (LUCCA et al 2015;SOLDA et al 2016;FERRAZ et al 2018;CEZARO et al 2018;RAMOS, 2019), Região sudeste: 3 a 36,05% (SILVA et al 2012;NEVES, 2014;PACHECO, 2015;YAMADA, 2016;RAMOS, 2019;NEVES et al 2020), Região Nordeste: 27% a 66% (DANTAS et al 2015e PEREIRA, 2019. Nas regiões Norte e Centro-Oeste não foram registrados dados sobre número de ovos de helmintos no período de 2012 a 2020.…”
Section: Resultsunclassified